Microwave-Assisted Green Synthesis and Biological Significance of Triazine Derivatives - Devi, Meenu; Yadav, Anjali; Alam, Muneer; Raghav, Sapna; Kumar, Ashish; Kaur, Navjeet (Current Organic Chemistry, 2026)
The microwave-assisted synthesis of 1,3,5-triaizne (2,4,6-trichloro-1,3,5-triazine), also known as TCT analogs, is described in this review article. The reactions of TCT with different compounds that have amine functional groups or hydroxy-substituted functional groups under microwave irradiation to produce the triazine derivatives are the main topic of this review article. The microwave irradiation technique has countless benefits over the heating method, such as fast reactions, reduced reaction time from hours to minutes, fewer by-products, improved or high yields, wide temperature instability range, regioselective products, and greater energy efficiency.
Keywords: triazine